Elementi di critica al concetto di psicoterapia scientifica - Salvador, Luca (Metapsychologica - rivista di psicanalisi freudiana, 2023)
This article critically analyzes the concept of scientific psychotherapy. It shows how a whole range of problems – which arise from studying both the specific psychotherapies and their multiform set – can be traced back, on the one hand, to the needs of promotion and self-justification by a group of professionals and on the other hand, to a series of preconceptions concerning the alleged special nature of the psychotherapies. In fact, in their therapeutic efficacy, the latter do not really differ from other traditional or religious forms of treatment. For a true critical discourse, it’s essential to restart by studying, without lobbying influences, the actual psychotherapeutic process.